2019
DOI: 10.15171/ehem.2019.26
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of BTEX from indoor air by Hyrcanian plants

Abstract: Background: Phytoremediation is one of the available and simple techniques for removing benzene, toluene, ethylbenzene, and xylene (BTEX) from indoor air. This study aimed to evaluate phytoremediation of low concentrations of BTEX by Hyrcanian plants including Ruscus hyrcanus and Danae racemosa. Methods: The test chamber was used to evaluate the removal of BTEX. Benzene, toluene, ethylbenzene, and xylene were injected into the chamber using Gastight syringes (Hamilton) to generate the concentration of 10 (benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…High levels of polycyclic aromatic hydrocarbons (PAHs) in the soil can induce tumors, reproductive, development, and immunological problems in terrestrial invertebrates [45]. BTEX (benzene, toluene, ethylbenzene, and xylene) can harm a person's personal neurological system, liver, kidneys, and respiratory system [46]. Pollutants obstruct soil pores, alter the content and structure of soil organic matter, diminish the activity and variety of soil microbes and plants, and, as a result, endanger human health via the food chain [47].…”
Section: Toxic Effects Of Petroleum On the Environmentmentioning
confidence: 99%
“…High levels of polycyclic aromatic hydrocarbons (PAHs) in the soil can induce tumors, reproductive, development, and immunological problems in terrestrial invertebrates [45]. BTEX (benzene, toluene, ethylbenzene, and xylene) can harm a person's personal neurological system, liver, kidneys, and respiratory system [46]. Pollutants obstruct soil pores, alter the content and structure of soil organic matter, diminish the activity and variety of soil microbes and plants, and, as a result, endanger human health via the food chain [47].…”
Section: Toxic Effects Of Petroleum On the Environmentmentioning
confidence: 99%
“…Most prominent hydrocarbons and metals include polycyclic aromatic hydrocarbons, Cd, Ni, Pb, Zn, Cr, and so forth can accumulate at high concentrations in soils, plants and animals thus ultimately can impact their health. They are the cause of tumors, neurological disorders, malfunctioning of kidneys and liver and can also impact biological processes in soil [25, 26]. This study found the accumulation of higher amounts of hydrocarbons and metals in soil contaminated with petroleum.…”
Section: Discussionmentioning
confidence: 98%
“…This can contribute to the carcinogenic effects and other possible health impacts of BTEX compounds. It is important to minimize exposure to these compounds to reduce the risk of adverse health effect [23][24][25].…”
Section: Xylene Metabolismmentioning
confidence: 99%